2002
DOI: 10.1046/j.1365-2168.89.s.1.3_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast 01

Abstract: Aims: The success of the ‘Sentinel Node Biopsy’ (SNB) in determining the axillary lymph node status necessitates an accurate and rapid method for intraoperative examination of the nodes in order to selectively operate on positive axillae during the same operative session. The aim of the study was to determine the feasibility and accuracy of IHC stained touch imprints in detecting axillary nodal metastases intraoperatively. Three hundred and forty‐four axillary nodes from 30 patients [23 axillary node clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For the first step of the SVM optimisation only a subset of the training data was used in order to maintain a manageable training time. For the linear kernel the first parameter approximation showed that a C of 2 7 results in the highest LOOCV of 75.4%. A second parameter optimisation was carried for further optimising the previously estimated C. For this search the range of C was set from 2 6 to 2 8 with an increase of 2 0.25 and the whole training set was used.…”
Section: Model Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first step of the SVM optimisation only a subset of the training data was used in order to maintain a manageable training time. For the linear kernel the first parameter approximation showed that a C of 2 7 results in the highest LOOCV of 75.4%. A second parameter optimisation was carried for further optimising the previously estimated C. For this search the range of C was set from 2 6 to 2 8 with an increase of 2 0.25 and the whole training set was used.…”
Section: Model Trainingmentioning
confidence: 99%
“…6 Alternatively, methods have been developed to allow faster intraoperative assessment of lymph nodes. These methods, including imprint cytology 7,8 and frozen section analysis, 9 also showed wide variations in the accuracy of detecting metastasis when compared with traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…The processing of samples is accelerated for these techniques, involving an analysis time of approximately 30–60 minutes. Yet, both approaches report wide variation in their sensitivity to detect cancerous lesions: detection levels as low as 44% and as high as 93% when compared with conventional histology 713. These variations indicate that such methodologies do not solve the problems associated with screening lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, this procedure is more time consuming and costly, and still relies on human microscopic inspection of the stained tissue for detection. Alternative techniques have been employed to facilitate faster intra-operative diagnosis of sentinel nodes, including imprint cytology, 7,8 and frozen section analysis. 9,10 The processing of samples is accelerated for these techniques, involving an analysis time of approximately 30-60 minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation